Selling and buying sex in the city: men who have sex with men in the Bangkok men who have sex with men Cohort Study. (March 2019) - Dunne, Eileen F; Pattanasin, Sarika; Chemnasiri, Tareerat; Varangrat, Anchalee; Raengsakulrach, Boonyos; Wichuda, Sukwicha; Ungsedhapand, Chaiwat; Sirivongrangson, Pachara; Chitwarakorn, Anupong; Holtz, Timothy H
We describe participants in the Bangkok Men who have sex with men Cohort Study (BMCS) who sold or bought sex. Men who have sex with men (MSM) and transgender women aged ≥18 years had HIV testing and behavioral data collected at enrollment and every four months. We evaluated report of receiving money or goods for sex (selling sex) or giving money or goods for sex (buying sex) at enrollment using logistic regression models; we also describe sex work over time, and HIV and syphilis incidence among those who report sex work. At enrollment, 511 (29.3%) of 1744 participants reported buying or selling sex. Factors associated with selling sex were young age, lower education, living alone or living with a friend, being unemployed, higher HIV knowledge, binge drinking and club drug use, a higher number of casual male partners, meeting sex partners at specific venues, having a foreign sex partner, and being HSV-1 seropositive. MSM aged 18–21 years who sold sex had an HIV incidence of 11.1 per 100 person-years (95% CI: 6.7–17.4). Almost one-third of participants from BMCS reported sex work at enrollment. Young men who sold sex had high HIV incidence and HIV prevention interventions are needed for this at-risk population in Bangkok, Thailand.